2012
DOI: 10.1364/oe.20.024600
|View full text |Cite
|
Sign up to set email alerts
|

Ultralow-power all-optical processing of high-speed data signals in deposited silicon waveguides

Abstract: Utilizing a 6-mm-long hydrogenated amorphous silicon nanowaveguide, we demonstrate error-free (BER < 10(-9)) 160-to-10 Gb/s OTDM demultiplexing using ultralow switching peak powers of 50 mW. This material is deposited at low temperatures enabling a path toward multilayer integration and therefore massive scaling of the number of devices in a single photonic chip.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
19
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 47 publications
(19 citation statements)
references
References 26 publications
0
19
0
Order By: Relevance
“…In recent years, several research groups have demonstrated superior nonlinear optical properties of a-Si:H with respect to c-Si in the 1.5-µm telecom band, and have used this to demonstrate ultralow power wavelength conversion [12], and spectral broading due to self-phase modulation [6]. All-optical switching has been demonstrated in c-Si microring resonators [16], but, to the best of our knowledge, it has not been reported in integrated a-Si:H microresonators of any kind.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In recent years, several research groups have demonstrated superior nonlinear optical properties of a-Si:H with respect to c-Si in the 1.5-µm telecom band, and have used this to demonstrate ultralow power wavelength conversion [12], and spectral broading due to self-phase modulation [6]. All-optical switching has been demonstrated in c-Si microring resonators [16], but, to the best of our knowledge, it has not been reported in integrated a-Si:H microresonators of any kind.…”
Section: Discussionmentioning
confidence: 99%
“…Investigations of nonlinear properties have focused either on characterization of material nonlinearity through self-phase modulation experiments [6], pump-probe experiments to characterize waveguides [7,8], or fourwave mixing for wavelength conversion [9,10]. There have also been recent demonstrations of parametric amplification [11] and low-power optical frequency conversion of optical data signals [12].…”
Section: Introductionmentioning
confidence: 99%
“…Here, by carefully controlling the geometry of a hydrogenated amorphous silicon waveguide for near-zero GVD at the pump wavelength, we demonstrate optical amplification over more than 440 nm (55 THz). This represents the largest parametric gain bandwidth yet demonstrated in either c-Si or a-Si:H nanowaveguides.The a-Si:H waveguide is fabricated using standard CMOS manufacturing techniques as detailed in [7]. The cross-section of the fabricated waveguide is 198 nm x 500 nm and the waveguide length is 6 mm.…”
mentioning
confidence: 99%
“…The a-Si:H waveguide is fabricated using standard CMOS manufacturing techniques as detailed in [7]. The cross-section of the fabricated waveguide is 198 nm x 500 nm and the waveguide length is 6 mm.…”
mentioning
confidence: 99%
“…Lower switching energies have been achieved in c-Si photonic crystal resonant cavities [20], but the operating bandwidth is inherently limited due to the resonant cavity structure. Due to the ultra-high nonlinearity of a-Si:H, error-free demultiplexing of a 160-Gb/s OTDM data signal to a 10 Gb/s stream in a 6-mm-long nanowaveguide using ultra-low peak powers of only 50 mW for the switching pump pulse has been achieved [21], representing a reduction in the power requirement by 1 order of magnitude over other CMOS-compatible approaches and can be translated to an energy consumption of 95 fJ/bit (see Fig. 3).…”
Section: A Signal Translationmentioning
confidence: 99%